2020
DOI: 10.2147/dddt.s207743
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Updated Systematic Review With Meta-Analysis Of Randomized Trials On Topical Cyclosporin A For Dry-Eye Disease</p>

Abstract: Background/Aims: To evaluate the effects of topical cyclosporin A (CsA) and artificial tears (ATs) for treating patients with dry-eye disease (DED). Methods: On January 25, 2019, five electronic databases and reference lists were searched for randomized clinical trials (RCTs) comparing CsA with ATs among patients with DED. The search strategy had no restriction on language or time. Two authors extracted surgery, mean age, anesthesia for Schirmer's test, tear-breakup time, Schirmer's test score, fluorescein-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Later, the United States Food and Drug Authority approved cyclosporine as a treatment option for moderate to severe DED. A systematic review and meta-analysis in 2020 concluded that cyclosporine had substantial e cacy for treating DED that was, nevertheless, attenuated upon combining it with arti cial tears (17). A Cochrane review had low-certainty evidence on whether cyclosporine and arti cial tears combination had a superior effect on reducing the symptoms and signs of DED in comparison to arti cial tears monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the United States Food and Drug Authority approved cyclosporine as a treatment option for moderate to severe DED. A systematic review and meta-analysis in 2020 concluded that cyclosporine had substantial e cacy for treating DED that was, nevertheless, attenuated upon combining it with arti cial tears (17). A Cochrane review had low-certainty evidence on whether cyclosporine and arti cial tears combination had a superior effect on reducing the symptoms and signs of DED in comparison to arti cial tears monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although the prescribing information for the most common topical prescription medications, cyclosporine A and lifitegrast, suggests these drugs are effective in both younger and older patients, 20 , 21 a recently published meta-analysis suggests that cyclosporine A may be more effective in a relatively older population. 22 Given the multifactorial and heterogenous nature of dry eye disease, there is a need to better characterize whether a treatment response to therapy is assessed across specific groups of patients and determine if the data demonstrate consistency of treatment effect outcomes across diverse patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Other approved prescription pharmaceutical treatment options for dry eye disease that act via reducing associated inflammation have shown mixed results regarding concomitant artificial tear use. A recent systematic review and meta-analysis found that cyclosporine A had reduced treatment effects when combined with artificial tears, 22 which suggests that there may be a potential washout effect. In addition, the prescribing information for cyclosporine A recommends use with artificial tears as long as there is at least 15 minutes between treatments, 20 which may complicate patient treatment administration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies retrieved did not differentiate between various levels of dry eye severity. The latest systematic review ( Tuan et al, 2020 ) ( n = 1085, 11 RCTs, moderate certainty evidence, Supplementary Table S25 ) showed that 0.05% cyclosporine eye drops alone or in combination with artificial tears could improve dry eye symptoms better than artificial tears alone. Still, the incidence of treatment-related adverse events is high, such as burning pain and stabbing pain.…”
Section: Actionable Recommendationsmentioning
confidence: 99%